2002
DOI: 10.2466/pms.2002.95.3f.1179
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory Factor Analysis of the Sport Orientation Questionnaire and the Task and Ego Orientation in Sport Questionnaire in a Japanese Sport Setting

Abstract: This study examined sport achievement orientation within the japanese sport setting. 1,836 male and 425 female athletes (M age = 18.6 yr.) from 47 sports completed the Japanese version of the Sport Orientation Questionnaire (24 items), and 1,781 males and 421 females (M age = 18.6 yr.) from 47 sports completed that of the Task and Ego Orientation in Sport Questionnaire (14 items). While the original English versions of the questionnaires are composed of three and two factors, respectively, present exploratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 9 publications
0
4
0
4
Order By: Relevance
“…El TEOSQ ha mostrado propiedades psicométricas adecuadas en diferentes contextos (Cindi & Koenraad, 2005;Duda et al, 1995;Goudas, Biddle & Fox, 1994;López-Walle, Balaguer, Meliá, Castillo & Tristán, 2011;Todorovich & Curtner-Smith, 2002;Wakayama, Watanabe & Inomata, 2002).…”
Section: Medición De Las Orientaciones Motivacionales En El Ejerciciounclassified
See 1 more Smart Citation
“…El TEOSQ ha mostrado propiedades psicométricas adecuadas en diferentes contextos (Cindi & Koenraad, 2005;Duda et al, 1995;Goudas, Biddle & Fox, 1994;López-Walle, Balaguer, Meliá, Castillo & Tristán, 2011;Todorovich & Curtner-Smith, 2002;Wakayama, Watanabe & Inomata, 2002).…”
Section: Medición De Las Orientaciones Motivacionales En El Ejerciciounclassified
“…El TEOSQ ha mostrado una adecuada validez y fiabilidad en diferentes países al usarse en contextos deportivos (e.g., Cindi & Koenraad, 2005;De Andrade, Salguero, González-Boto & Márquez, 2008;Li, Harmer, Chi & Vongjaturapat, 1996;Wakayama et al, 2002). Como hemos mencionado anteriormente, en un contexto español de EF, la herramienta muestra también adecuadas propiedades psicométricas (Peiró & Sanchis, 2004).…”
Section: Generalización Interculturalunclassified
“…The World Health Organization warns individuals that physical inactivity can increase the risk of cancer, heart disease, stroke, and diabetes by 20-30% and shorten their lifespan by 3-5 years (6). Studies showed that in the United States (7), Canada (8), Germany (9), Spain (10), Portugal (11), Australia (12), Japan (13), and China (14,15), the lack of exercise motivation was the main reason for college students' physical inactivity.…”
Section: Introductionmentioning
confidence: 99%
“…There is already a large amount of published literature that has examined sport orientation and sport motivation that focuses on goal orientation or achievement motivation constructs (Dweck, 1986;Maehr and Braskamp, 1986;Vealey, 1986;Stipek, 1988;Nicholls, 1989;Ames, 1992;Roberts, 1992;Duda, 1993;Treasure and Roberts, 1994). Past research has used both exploratory (Duda, 1989;Duda and White, 1992;Newton and Duda, 1993;Kim and Gill, 1997;Skordilis et al, 2001;Wakayama et al, 2002;Tari-Keresztes et al, 2015) and confirmatory (Kang et al, 1990;Li and Tang, 1990;Seifriz et al, 1992;Hayashi and Weiss, 1994;Marsh, 1994;Chi and Duda, 1995;Duda, 1995;Lerner and Locke, 1995;Skordilis et al, 2001;Hanrahan and Biddle, 2002) factor analysis to test the construct of the Gill's SOQ. However, sample participants have been largely sourced from the United States, Australia, or the European Union.…”
Section: Introductionmentioning
confidence: 99%